Perovskite nickelates as bio-electronic interfaces - Hai-Tian Zhang (Nature Portfolio, 2019)
Functional materials that act as bio-sensing media when interfaced with complex bio-matter are attractive for health sciences and bio-engineering. Here, the authors report room temperature enzyme-mediated spontaneous hydrogen transfer between a perovskite quantum material and glucose reactions.